Beyond biotechnology : the barren promise of genetic engineering - Holdrege, Craig, 1953- (Culture of the land., 2008)
The Human Genome Project announced in 2003 that it had successfully mapped the human DNA. Scientists, politicians, theologians, and pundits speculated what would follow. Beyond Biotechnology: The Barren Promise of Genetic Engineering distinguishes between hype and reality, examining the delicate relationship between science and nature. Authors Craig Holdrege and Steve Talbott evaluate the current state of genetic science and examine its potential applications, as well as possible dangers. The authors illustrate how the popular view of genetics does not include an understanding of how genes wor.